Analysis the effect of Diffraction Phenomena by Complex Shapes with Hybrid MOM-GTD Method - Mendil Samir; Aguili Taoufik (International Journal of Engineering Education, 2019)
This article deals with a hybrid method combining the method of moments (MOM) with the general theory of diffraction (GTD). This hybrid approach is used to analyze antennas located near perfectly Bodies of arbitrary curved shape. Some examples, e.g. an antenna mounted near a perfect conductor cylinder with two plates, demonstrates that the hybrid approach is the most suitable technique for modeling large-scale objects and arbitrary shapes. This approach allows us to resolve the problem, that the other methods can’t solve it alone. Generally, random radiation locates on or near an arbitrary form, can be solved using this technique hence the strong advantages of our method.